The role of glycine betaine in range expansions; protecting mangroves against extreme freeze events. (18th July 2019) - Hayes, Matthew A.; Shor, Audrey C.; Jesse, Amber; Miller, Christopher; Kennedy, John P.; Feller, Ilka
Abstract: Due to a warming climate, mangrove populations within the Gulf of Mexico and along the Florida Atlantic coastline are expanding their range poleward. As mangroves expand their range limit, leading edge individuals are more likely to experience an increased incidence of freeze events. However, we still lack a clear understanding of the mechanisms used by mangroves to survive freezing conditions. Here, we conducted common garden experiments at different locations experiencing variable winter freeze conditions to show glycine betaine, an organic osmolyte, increases significantly with freeze exposure, playing an important role in the freeze tolerance of Avicennia germinans, a widespread Neotropical mangrove. We found glycine betaine accumulation was similar across all source populations and freeze exposure locations, suggesting glycine betaine is not a range limit adaptation and is instead used for freeze tolerance by A. germinans irrespective of source population. Plants sourced from populations that experience freezing conditions exhibited greater rates of survival, indicating range edge populations of A. germinans have other heritable adaptations in addition to glycine betaine for freeze tolerance. Synthesis . Continued mangrove expansion poleward will result in a greater incidence of freeze events for individuals at the leading edge. Our findings suggest freeze tolerance in this species may be genetically based and that leading edge A. germinans have the potential to survive extreme freeze events and recover post‐freeze, allowing for their continued expansion poleward. This process of selective survival may act to promote adaptation of freeze tolerance in range edge populations. Abstract : Continued mangrove expansion poleward will result in a greater incidence of freeze events for individuals at the leading edge. Our findings suggest freeze tolerance in this species may be genetically based and that leading edge Avicennia germinans have the potential to survive extreme freeze events and recover post‐freeze, allowing for their continued expansion poleward. This process of selective survival may act to promote adaptation of freeze tolerance in range edge populations.